Resiliensi Ekonomi Kelompok Nelayan Perikanan Tangkap Kawasan Perkotaan - Andreas Novianto; Sriati Sriati; Dadang Hikmah Purnama (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
This article was motivated by a decline in the sales of fishery catches for fishermen in urban areas, and it posed challenges in meeting aspects of meeting daily needs. The purpose of this study was to see how fishermen adapt to resilience and face challenges from problems that arise during the pandemic and had an impact on decreasing capture fisheries marketing results. This study used the Buheji Economic Resilience approach (2018), namely the ability to understand a problem faced by the community from uncontrolled conditions. The research method used a qualitative data analysis unit, namely the fishermen group. Data collection techniques through observation, interviews, and documentation. The results of this study showed that the economic resilience of fishermen groups showed that there were differences in the process of carrying out their resilience, depending on the capacity of each fisherman. With this, they had different forms of resilience strategies in fulfilling their needs, so they had diverse livelihood activities to meet their needs such as changing livelihoods, managing catches and adding livelihoods.